Social housing – between design and social practices: The case of the 670 social housing units in Oran - Bachir Benyamina; Sidi Mohammed el Habib Benkoula (Architecture Papers of the Faculty of Architecture and Design STU, 2024)
Housing represents the initial place where each individual has the opportunity to reconnect with their identity. It should offer every family the opportunity to live according to their lifestyle. Most people aspire to a living space that reflects both their aspirations and their way of life, while also taking into account the demands of everyday life. Since independence, Algeria has shown a remarkable commitment to promoting social housing, mobilising significant efforts in this area. However, what has been observed is that professionals design housing that occupants adapt to their daily needs. Despite the in-depth analyses by numerous researchers revealing the significance of these transformations, professionals persist in reproducing the same spatial patterns, thus demonstrating a certain indifference towards the work of academic research. Residents have tried to adapt to these housing units by making modifications to gain more space both inside and out. Inside, these transformations were appreciated by the occupants. From the outside, these remodellings have had a negative impact on the overall image of the city. The balance between quantity and quality was not taken into account, even though the aim of rapid construction was to alleviate pressure on the housing market. This article aims to question occupants' practices to establish a link between the housing designed and built, and occupants' expectations. The analytical approach used is post occupancy evaluation (POE) - a multi-method approach to data collection that includes direct observation, plan analysis and questionnaire. The housing units studied were not selected according to any particular method but rather chosen on the basis of the residents who agreed to answer the questions and share their lifestyle and expectations regarding their housing. Data processing, through a comparison between the initial plan drawn up by the designer and the current plan modified by the inhabitant, enabled us to deduce the discrepancies that exist between the two plans and to understand the modes of appropriation of the housing's interior space.